Trust and Responsibility in Islam: Integrating Qur’anic and Hadith Perspectives with Family Issues, Anti-Corruption Leadership, and Islamophobia - Elvina Rahma Sari Putri; Habibatur Rasyidah; Maulidheyna Bayora (CV. Jalan Cendikia, 2026)
This study examines the concept of responsibility in maintaining trust through the perspective of Quranic verses and hadiths and their integration with contemporary social, family, and religious issues. Using a qualitative approach based on literature study, this article analyzes three focuses: parental responsibility in the family based on QS. At-Tahrim verse 6 integrated with the concept of life balance; leadership in QS. Al-An'am: 70 which is associated with anti-corruption leadership; religious responsibility in QS. An-Nisa: 36 analyzed in relation to the phenomenon of Islamophobia. The results of the study indicate that the teaching of trust in Islam provides a normative foundation for personal, social, and collective obligations. The hadiths studied strengthen this Quranic mandate while providing practical behavioral guidelines. The integration of this teaching with modern challenges proves that Islamic values ​​remain relevant and applicable in the contemporary context. This article argues that internalizing the value of trust can serve as a moral antidote to family dysfunction, political corruption, and religious intolerance among Muslims today.